Global trends in caffeine-based lifestyles: a citespace exploration of potential environmental sustainability impacts - Razali, Siti Mardhiyah; Masimen, Mohammad Asyraf Adhwa; Husain, Noreen; Idris, Izwandy; Wan Ismail, Wan Iryani; Abdul Hamid, Hisyam (Faculty of Pharmacy, 2025)
Caffeine-based lifestyles have become increasingly common, reflecting its widespread consumption as a psychoactive stimulant found naturally in coffee, tea and cocoa yet synthetically in personal care products (PCPs) and pharmaceuticals. This trend has raised concerns about its potential environmental consequences as it can bioaccumulate in various species, including aquatic organisms and terrestrial insects, prompting continuous research in this field since decades ago. However, a comprehensive bibliometric and scientometric analysis in this research field appears lacking. Thus, the primary goal of this study is to analyse the scientific literature concerning the impact of caffeine-based lifestyles on the environment. A CiteSpace analysis was applied in this study to determine various aspects of research literature, including the identification of productive authors, institutions, journals, regional distribution and emerging issues in the field. The study yielded 869 relevant publications from the Web of Science Core Collection (WOSCC) database. The results revealed that the United States, China, Canada, Brazil, and Spain were the top five countries out of 3345 writers from 108 countries active in this research area on the top of keywords such as PCPs, pharmaceutical and wastewater. The present study provides the existing body of knowledge on this topic by sharing a visual knowledge map, which highlights the trend, offering a valuable perspective, and opportunity for researchers.